2015
DOI: 10.1016/j.jad.2015.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and statin use and the subsequent development of depression in men and women: Results from a longitudinal population-based study

Abstract: Our data do not support a large scale preventive treatment of depression using aspirin or statins in subjects aged from 35 to 66 years from the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
0
38
1
Order By: Relevance
“…Our findings are in general agreement with those present in the literature, in which depressive symptoms do not appear to benefit from aspirin use. All studies, except one, reported that the use of aspirin was not associated with any favorable effect on depression. In comparison with these previous studies, the strength of our study includes the use of propensity score matching to further control for background sociodemographic variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in general agreement with those present in the literature, in which depressive symptoms do not appear to benefit from aspirin use. All studies, except one, reported that the use of aspirin was not associated with any favorable effect on depression. In comparison with these previous studies, the strength of our study includes the use of propensity score matching to further control for background sociodemographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding the possible impact of aspirin on depression is limited and unclear. Two observational studies did not find any significant association between the use of aspirin and the development of depression . An open‐label trial found that aspirin did not provide any benefit as a treatment for a current major depressive episode and was associated with several side effects when added to citalopram in 10 subjects with a diagnosis of MDD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in experimental models, SSRIs attenuate lipopolysaccharide-induced inflammation [91]. A variety of more traditional antiinflammatory therapies has also been used for the treatment of depression, including aspirin and other nonsteroidal antiinflammatory drugs, statins, and cytokine inhibitors like etanercept (which blocks TNF) [92][93][94][95]. Agomelatine is a a b c d member of a novel class of new antidepressants which are melatonin agonists; it has been approved by the European Union, after being shown to have similar efficacy to SSRIs for the treatment of depression [96,97].…”
Section: Therapeutic Approaches To the Treatment Of Depression: A Focmentioning
confidence: 99%
“…Some studies think that statins can inhibit cholesterol synthesis and further inhibit testosterone production, which may be one of the causes of ED (Corona, Boddi, Balercia, et al, ). The lipid solubility of statins affects the central nervous system and induces penis peripheral nerves dysfunction, which may be one of the causes of ED (Glaus, Vandeleur, Lasserre, et al, ). Previous studies had reported statins can induce depression (Monika, Fritz, Gunther, et al, ).…”
Section: Discussionmentioning
confidence: 99%